BENEFÍCIOS POTENCIAIS DE PLANTAS DANINHAS: UMA PERSPECTIVA DE EDUCAÇÃO AMBIENTAL - Schott, Patrícia Cati; Canto-Dorow, Thaís Scotti do (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The present paper aimed to carry out a different analysis of weeds found in the municipalterritory of Paraíso do Sul, researching and presenting its potential agronomical, medicinalor economic benefits. To do so, samples were collected from maize fields located in 10 areasin the countryside of the city. The species were identified, contributing to the review of theliterature. The following selected species were the most abundant ones: Amaranthus deflexusL., Bidens pilosa L., Commelina erecta L., Cynodon dactylon (L.) Pers., Cyperus hermaphroditus(Jacq.) Standl., Digitaria ciliaris (Retz.) Koeler, Digitaria nuda Schumach., Echinochloa colonum(L.) Link, Euphorbia heterophylla L., Galinsoga parviflora Cav., Polygonum punctatum Elliott,Portulaca oleracea L., Richardia brasiliensis B.A. Gomes, Scoparia dulcis L., Sida rhombifoliaL., Stemodia verticillata (Mill.) Hassl. e Urochloa plantaginea (Link) R.D. Webster. Based on thedata presented, we seek to encourage the public to change the common opinion about thesespecies. This study will serve to further environmental education.